Towards an AIDS free generation: Is stigma still an issue in Zambia? Results from a legal environment assessment of the HIV/AIDS/TB program of the Churches Health Association of Zambia - Godfrey Biemba; Dhally M. Menda; Yoram Siame; Karen Sichali Sichinga; William Macleod (AOSIS, 2020)
This paper reports on HIV related stigma based on results from an HIV legal environment assessment (LEA) within the Churches Health Association of Zambia HIV/AIDS program. We conducted 9 Focus Group Discussions and 20 Key Informant Interviews with key HIV/AIDS stakeholders that included representatives from network of Zambian people living with HIV. We administered a Survey Questionnaire to 337 people living with HIV (PLHIV) and 233 health workers. Quantitative data were analyzed using SAS v9.4; qualitative data was analyzed using QRS NVIVO version 11.0 Pro. Internalized stigma ranged between 20.8% and 31.8% of PLHIV; more among females than males. About one third (31%, n=104)) of the 337 participants reported that they were aware of being gossiped once, a few times, or often; more among females than males. 62.3%, 63.1%, and 55.1% of the 233 health workers said it was somewhat true or certainly true that in their catchment areas, PLHIV struggle to have an HIV test because of stigma, were hesitant to start ART due to stigma; told them that they had challenges taking their ARVs because of stigma respectively.